Study on the Development of Livable Settlement Areas in Tsunami Safe Areas in Padang City - Azani, Fadli Haikhal; Arif, Dian Adhetya (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The city of Padang is one of the areas that has a high level of vulnerability to tsunami disasters. People can anticipate tsunamis, one of which is by building houses in a tsunami safe zone, but before many people do this anticipation, it is best to test the habitability of the settlement. The aim of this research is to find out habitable settlements in the tsunami safe zone of Padang City. This research uses a quantitative descriptive method by utilizing the Geographic Information System through a weighting and scoring method for each indicator. The results of the analysis show that there are 5 classes of vulnerability with a very low level of vulnerability dominating 43,089 Ha or 64.62%, in settlements in accordance with the Padang City Regional Spatial Plan, counting 11 sub-districts with livable settlements in accordance with the results obtained through weight calculations and scoring in each indicator is 2,635 Ha or around 23.87% of the total settlements in the Padang City Regional Spatial Planning Plan.